ANALYSIS OF PROMOTION, PRODUCT, PRICE AND PLACE ON PATIENT SATISFACTION(STUDY AT AN INDEPENDENT PRACTICING DOCTOR LIES FADILAH PURWAKARTA DISTRICT) - Fadilah, Lies; Paramarta, Vip; Wirawan, Chevi (Organisasi Kreatif Indonesia Emas, 2024)
The marketing mix is ​​a very important part of an organization, namely a series of marketing tools that are well organized and used by a company to achieve marketing goals while meeting consumer needs and desires so as to create consumer satisfaction. This research was conducted to determine the effect of promotion, product, price and place on patient satisfaction (study at Independen Practice Doctor Dr. Lies Fadilah, Purwakarta Regency). The approach used in this research is a quantitative approach. The sample used was 110 patients seeking treatment at the Independen Practice Doctor Dr. Lies Fadilah, Purwakarta Regency. This research data was obtained from the results of filling out a questionnaire and analyzed using the Multiple Linear Regression analysis technique. The results of this research show that promotion, product, price and place influence patient satisfaction both partially and simultaneously in patients seeking treatment at the Independen Practice Doctor Dr. Lies Fadilah, Purwakarta Regency.